Forms of Violent Behavior in Patients with Mental Disorders at the University Psychiatric Clinic Ljubljana from 2018 to 2021 Using the OAS/BVC Scale Assessment—A Descriptive Study - Rok Hatze; Maja Šikić Pogačar; Jožica Peterka Novak; Branko Bregar (Slovenian Journal of Public Health, 2026)
Abstract Introduction The high incidence of violence directed at healthcare workers is a major public health concern. The purpose of the study was to investigate the incidence of various forms of aggression at the University Psychiatric Clinic Ljubljana from 2018 to 2021, stratified by perpetrator gender, time of occurrence, and ward type. Methods Data were collected using completed standardised forms (the OAS and BVC scales) during 2018–2021. A total of 4,392 episodes of various forms of violent behaviour were detected. Descriptive and bivariate statistics were performed using IBM SPSS. The level of statistical significance was set at p < 0.05. Results The total aggression score was significantly higher in men (t = 8.471, p < 0.001). Wards differed in the forms of aggressive behaviour (p < 0.05). The total aggression score (AS score) was significantly higher during the evening shift than during the morning shift (p < 0.001) or the night shift (p = 0.037). A positive correlation was found between OAS and BVC scores (r = 0.672, p < 0.001). Conclusions Our findings are consistent with previous international research, confirming that violence remains a common challenge in psychiatric inpatient settings. The positive association between BVC and OAS scores supports the complementary use of both instruments for violence risk assessment and incident evaluation. In line with previous research, the results support recommendations that violence prevention should extend beyond assessment tools and staff training to include a culture of safety and organisational commitment to preventing and managing aggression.